Construction and application effect of coach competency model in volleyball - Wang, Danyi; Bo, Xuesong (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Constructing a competence model for volleyball coaches tailored to school characteristics has recently gained importance. This study aimed to clarify the competency model construction and its application effect. The study developed a volleyball coach competence model centered on knowledge, skills, professional roles, attitudes, and motivation. A quantitative methodology was used to assess the relationships between these dimensions and coaching performance, emphasizing teaching quality and overall effectiveness. The model drew from theoretical frameworks, including the Iceberg Model and the Onion Model. The sample consisted of 120 volleyball coaches. The correlation analysis revealed significant relationships among knowledge competence, skill competence, professional role, work attitude, work motivation, educational process factors, and educational target factors (pY1 < 0.05, pY2 < 0.05, and r > 0.1). The regression results indicated that gender, professional title, knowledge competence, professional competence, professional role, and work attitude positively influenced the achievement of the competency application effect (p < 0.05 and β > 0). In contrast, work motivation, age, teaching experience, education level, and salary showed no statistically significant impact (p > 0.05). Volleyball coaches' competence is essential for effective teaching and training, directly enhancing athletes' skills and performance. The model also improves coaches' quality and application ability, leading to increased athlete satisfaction and better training outcomes.